Hubungan Perilaku Perawat dengan Penerapan Keselamatan dan Kesehatan Kerja (K3) di Instalasi Gawat Darurat RSD Gunung Jati Kota Cirebon - Fathur Rachman, Rizaldy; Iryadi, Roni; Erlisya Puspandani, Mitha (Jurnal Kesehatan Pertiwi, 2024)
Introduction: a service unit that deals with emergency patients, emergency rooms are high clinical risk areas. Based on data from the Mother Thamrin Hospital in Cirebon that in 2018 there were 2 cases of work accidents . Research Objectives: (sharp objects). Occupational Safety and Health (K3) efforts must be carried out in all workplaces, especially those with health risks such as hospitals. Occupational accidents can be caused by many factors, one of which is human resource behavior, which consists of knowledge, attitudes, and actions. The purpose of this study was to analyze the Research Methods: of Occupational Safety and Health (K3) in the ED. This type of research is quantitative with a cross sectional design. The study was conducted at Gunung Jati General Hospital in Cirebon. The study was conducted in May 2024. The study population was 38 people, all of them were sampled. Data were analyzed by univaria Results: of the study : test at the 95% confidence level (a = 0.05). Based on the results of the study showed that knowledge is related to the application of K3 at the Gunung Jati General Hospital in 2024, p = 0.003 <0.05. Attitudes related to the application of K3. Conclusion: Actions related to the application of K3 at the Gunung Jati General Hospital in 2024, p = 0.001 <0.05. The conclusion of this study is that nurses' knowledge, attitudes, and actions are related to the application of Occupational Safety and Health (K3).